Characterization of Age-Related Differences in the Human Choroid Plexus Volume, Microstructural Integrity, and Blood Perfusion Using Multiparameter Magnetic Resonance Imaging - Alisch, Joseph S. R.; Kiely, Matthew; Triebswetter, Curtis; Alsameen, Maryam H.; Gong, Zhaoyuan; Khattar, Nikkita; Egan, Josephine M.; Bouhrara, Mustapha (Frontiers in Aging Neuroscience, 2021)
The choroid plexus (CP) is an important cerebral structure involved in cerebrospinal fluid production and transport of solutes into the brain. Recent studies have uncovered the involvement of the CP in neurological disorders such as Alzheimer’s disease and multiple sclerosis. However, our understanding of human age-related microstructural and functional changes in the CP with aging and neuropathology is limited. In this cross-sectional study, we investigated age and sex differences in the CP structure and function using advanced quantitative magnetic resonance imaging methodology in a large cohort (n = 155) of cognitively unimpaired individuals over a wide age range between 21 and 94 years. Our analysis included volumetric measurements, relaxometry measures (T1 and T2), diffusion tensor imaging (DTI) measures of fractional anisotropy (FA) and mean diffusivity (MD), as well as measures of cerebral blood flow (CBF). Our results revealed that CP volume was increasing with advancing age. We conjecture that this novel observation is likely attributed to alterations in the CP microstructure or function as well as to ventriculomegaly. Indeed, we also found that CBF was lower with advanced age, while, consistent with previous studies, T1, T2 and MD were higher, and FA was lower with advanced age. We attribute these functional and microstructural differences to a deteriorated CP structural integrity with aging. Furthermore, our relaxometry and DTI measures were found to be associated with differences in blood perfusion revealing lower microstructural integrity with lower CBF. Finally, in agreement with literature, sex-related differences in MD and CBF were statistically significant. This work lays the foundation for ongoing investigation of the involvement of CP in neurodegeneration.